Bacterial quorum sensing degrader from biofloc and freshwater prawn, Macrobrachium rosenbergii associated with green microalgae Chlorella sp. - G., Nurarina; H., Aini; Ying, L. H.; Ahmad, I.; A. Rahim, A.; Md Yasin, Ina Salwany; Mohd Ikhsan, Natrah Fatin (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Quorum sensing is a cell-to-cell communication using signal molecules for the regulation virulence genes expression in bacteria. Interference with quorum sensing using QS degrader strains is currently being investigated to fight bacterial diseases. In this study, two potential strains of quorum sensing (QS) degrader were successfully isolated from biofloc and giant freshwater prawn, Macrobrachium rosenbergii. The strains were identified as Bacillus subtilis, BP-BFT/1b and Bacillus cereus, BP-MBRG/1b. Meanwhile, Chlorella sp. was made axenic using 13 to 500 ppm of different antibiotic mixtures (chloramphenicol, tetracycline, enrofloxacin, kanamycin, and neomycin) in which the interaction of the algae with different QS degrader strains, different microbial communities and pathogenic bacterium Aeromonas hydrophila were investigated. Growth of Chlorella sp. added with Bacillus subtilis, BP-BFT/1b was higher compared to Bacillus cereus, BP-MBRG/1b. The results showed that the growth of axenic Chlorella sp. was improved in the presence of bacteria, including the bacterial QS degraders. Hence, there is a potential to incorporate both microorganisms in aquaculture systems to overcome invasion of pathogenic bacteria through bacterial QS degrading mechanism.